BUCHET, CHRISTIAN & VERGÉ-FRANCESCHI, MICHEL (DIR.). LA MER, LA FRANCE ET L´AMÉRIQUE LATINE. - Marília de Azambuja Ribeiro (Clio: Revista de Pesquisa Histórica, 2015)
BUCHET, CHRISTIAN & VERGÉ-FRANCESCHI, MICHEL (DIR.). LA MER, LA FRANCE ET L´AMÉRIQUE LATINE.